Analisis Profitabilitas, Struktur Modal, dan Ukuran Perusahaan terhadap Nilai Perusahaan (Literature Review) - Karisa Maslaka (Universitas Multi Data Palembang, 2026)
This study aims to explain the influence of profitability, debt policy, and company size on company value through a literature review approach. Company value is proxied by Price to Book Value (PBV), which reflects market perception of the company's performance and prospects. The method used is qualitative, analyzing various studies from national scientific journals. The results of the study indicate that profitability tends to have a positive effect on company value because it indicates the ability to generate profits and increase investor confidence. Debt policy can reduce company value when the level of leverage is high due to increased financial risk. Meanwhile, company size shows mixed findings and is therefore not always the primary basis for investment decisions. These findings highlight the importance of effective financial management in shaping market valuations.